2020
DOI: 10.1063/5.0009639
|View full text |Cite
|
Sign up to set email alerts
|

Toward clinical elastography of dermal tissues: A medical device to probe skin’s elasticity through suction, with subsurface imaging via optical coherence tomography

Abstract: The mechanical behavior of dermal tissues is unarguably recognized for its diagnostic ability and in the last decades received a steadily increasing interest in dermatology practices. Among the various methods to investigate the mechanics of skin in clinical environments, suction-based ones are especially noteworthy, thanks to their qualities of minimal invasiveness and relative simplicity of setups and data analysis. In such experiments, structural visualization of the sample is highly desirable, both in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Frequency-dependent shear wave speed plots of each volunteer skin region were fit the Voigt speed dispersion model (5) as shown in Fig. 4 for both anatomic sites, together with the average of all fitting curves.…”
Section: Doppler Motion Frames Representing Crawling Wavementioning
confidence: 99%
See 1 more Smart Citation
“…Frequency-dependent shear wave speed plots of each volunteer skin region were fit the Voigt speed dispersion model (5) as shown in Fig. 4 for both anatomic sites, together with the average of all fitting curves.…”
Section: Doppler Motion Frames Representing Crawling Wavementioning
confidence: 99%
“…Several studies have reported the use of elastography methods for characterizing the skin elasticity, including skin suction [4,5], the use of a twistometer [6], the measurement of the strain-stress relationship [7], and the propagation of mechanical waves [3]. This latter technique, also called wavebased elastography, has shown great potential for the viscoelastic characterization of in vivo skin tissues using supersonic shear imaging (SSI) [8], shear wave elastography [3,9], acoustic radiation force imaging (ARFI) [10], and crawling wave elastography [11].…”
Section: Introductionmentioning
confidence: 99%